AN ANALYSIS OF READING MATERIALS IN “INTERLANGUAGE: ENGLISH FOR SENIOR HIGH SCHOOL STUDENTS XI (SCIENCE AND SOCIAL STUDY PROGRAMME)” PUBLISHED BY THE NATIONAL EDUCATION DEPARTMENT AS AN IMPLEMENTATION OF THE 2006 ENGLISH STANDARD COMPETENCE (RETAIN, 2013)
Abstract This study is conducted to describe the conformity of reading activites with the reading indicators as stated in SKL UN 2012, to describe the relevance of text types in the reading materials to the 2006 English standard competence based on each text type characteristics’, and to describe the appropriateness of the linguistic features of reading materials in the textbook with the standard competences in the 2006 English standard competence. This study was designed as a documentary analysis in the form of descriptive qualitative research without any statistical calculation. The result of this analysis showed that all of reading materials are not relevant with the 2006 English standard competence. It does not provide any explanations, examples, and exercises in order to make the students really understand about the texts being learned.   Keywords: analysis, reading materials, textbook, the 2006 English standard competence, SKL UN 2012, generic structure, and linguistic feature.